2001
DOI: 10.1034/j.1600-0420.2001.790506.x
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma in East Greenlandic Inuit

Abstract: ABSTRACT.Purpose: To determine the prevalence of primary angle-closure glaucoma (PACG) in an isolated Greenlandic Inuit community and to examine the anatomical risk factors for this disease. Methods: All individuals aged Ø40 years were examined. Visual acuity, refractive error, anterior chamber depth (ACD), intraocular pressure (IOP), gonioscopy, and optic disc characteristics were recorded. Results: Seventy-nine individuals (65% response rate) were examined. Mean IOP was 12.0 mmHg. ACD was shallow and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The “glaucoma suspects and cases” that were excluded on the basis of abnormal psychophysical testing, IOP or gonioscopy were older than those in the “normal dataset” which is unsurprising as visual field defects, occludable angles22 23 and ocular hypertension24 are more common in older age groups. The “glaucoma suspects” were no different from the “normal” subjects in terms of mean optic disc area, disc diameter or total rim area.…”
Section: Discussionmentioning
confidence: 99%
“…The “glaucoma suspects and cases” that were excluded on the basis of abnormal psychophysical testing, IOP or gonioscopy were older than those in the “normal dataset” which is unsurprising as visual field defects, occludable angles22 23 and ocular hypertension24 are more common in older age groups. The “glaucoma suspects” were no different from the “normal” subjects in terms of mean optic disc area, disc diameter or total rim area.…”
Section: Discussionmentioning
confidence: 99%
“…The highest rates are reported in Inuit, Chinese, and other Asian populations; lower rates are reported in populations of African and European origin. The incidence of ACG in Caucasian population is between 0.1% and 0.6%, in the Inuit population between 2.2% and 6.2%, and in Asia between 0.3% and 3% (Arkell et al, 1987;Bonomi et al, 1998;Bourne et al, 2001;Congdon et al, 1992Congdon et al, , 1996Day et al, 2012;Shiose et al, 1991).…”
Section: Epidemiologymentioning
confidence: 93%
“…15 Use of ultrasonic and, more recently, OCT imaging devices has shown the shallowing of anterior chamber that occurs with age; however, findings of recent studies have shown no clearly greater proportion of persons among Chinese individuals with shallower anterior chamber depth compared with European and African populations. 16 Quigley 17 and associates have opened an interesting angle of research in this area by showing unfavourable physiological behaviour of the iris in individuals susceptible to angle-closure glaucoma.…”
Section: Cambridge Ophthalamological Symposiummentioning
confidence: 97%